2012
DOI: 10.1159/000335299
|View full text |Cite
|
Sign up to set email alerts
|

CD10 Is Inversely Associated with Nuclear Factor-Kappa B and Predicts Biochemical Recurrence after Radical Prostatectomy

Abstract: Introduction: The cell surface endopeptidase CD10 (neutral endopeptidase) and nuclear factor-ĸB (NF-ĸB) have been independently associated with prostate cancer (PC) progression. We investigated the correlations between these two factors and their prognostic relevance in terms of biochemical (prostate-specific antigen, PSA) relapse after radical prostatectomy (RP) for localized PC. Patients and Methods: The immunohistochemical expression of CD10 and NF-ĸB in samples from 70 patients who underwent RP for localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…The pan-Canadian multi-centre cohort is an important addition to PC research to support the validation of potential biomarkers that have been reported from studies using small cohorts from single institutions. Previously, we and others have shown that overall p65 expression, or more specifically its nuclear frequency in PC, is associated with BCR in single institution cohorts [814,2123]. Here, we identified a threshold of p65 nuclear expression in a multi-centre cohort of 250 PC patients and validated this prognostic biomarker in a second independent multi-centre cohort of 1,262 PC patients.…”
Section: Discussionsupporting
confidence: 57%
“…The pan-Canadian multi-centre cohort is an important addition to PC research to support the validation of potential biomarkers that have been reported from studies using small cohorts from single institutions. Previously, we and others have shown that overall p65 expression, or more specifically its nuclear frequency in PC, is associated with BCR in single institution cohorts [814,2123]. Here, we identified a threshold of p65 nuclear expression in a multi-centre cohort of 250 PC patients and validated this prognostic biomarker in a second independent multi-centre cohort of 1,262 PC patients.…”
Section: Discussionsupporting
confidence: 57%
“…In line with these opposing effects, the prognostic significance of NEP expression may vary between different tumor types. For example, NEP expression is a favorable prognostic factor in hepatocellular carcinoma19 and diffuse large B cell lymphoma,9 whereas it predicts poor outcome in prostate cancer, renal carcinoma, breast cancer, and endocrine pancreas cancer 10,11,17. According to our data in the current study, NEP expression was dramatically upregulated in IHCC tissues compared with noncancerous liver tissues.…”
Section: Discussionsupporting
confidence: 58%
“…Stromal CD10 expression was reported to correlate with poor prognosis in pancreatic cancer [ 13 ], breast cancer [ 14 ], and gastric carcinoma [ 15 ]. Similarly, tumor expression of CD10 has been reported to promote tumor progression in colorectal cancer [ 16 ], prostate cancer [ 17 20 ], bladder cancer [ 21 ], and melanoma [ 3 ]. On the other hand, CD10 has also been reported to inhibit tumor progression in cervical carcinoma [ 22 ] and ovarian cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%